Correlative factors associated with the recurrence of ovarian endometriosis: a retrospective study - Xi-Wa Zhao; Meng-Meng Zhang; Jian Zhao; Wei Zhao; Shan Kang (Clinical and Experimental Obstetrics & Gynecology)
Background: The aim of this study was to confirm and analyze the correlative factors that could influence the recurrence of ovarian endometriosis after conservative surgery, including both risk and protective factors. Methods: From January 2010 to January 2018, a retrospective study was conducted which included 1080 patients with ovarian endometriosis who received a minimum of 2 years of follow-up after conservative surgery at a university-based tertiary care hospital. Recurrence was defined as the presence of ovarian cysts larger than 2 cm detected by ultrasonography within 2 years after surgery. The effects of twenty correlative variables on recurrence were evaluated. Results: The cumulative 2-year recurrence rate of ovarian endometriosis after conservative surgery was 15%. According to the logistic regression analysis, the significant risk factors that were independently associated with high recurrence of endometriosis were previous medical treatment of endometriosis (odds ratio [OR] = 2.06; 95% confidence interval [95% CI] = 1.27–3.34; P = 0.004), painful nodules in the pouch of Douglas (OR = 2.44; 95% CI = 1.23–4.85; P = 0.011), largest cyst diameter (OR = 1.54; 95% CI = 1.08–2.18; P = 0.016) and bilateral ovarian involvement (OR = 1.69; 95% CI = 1.19–2.39; P = 0.003). Moreover, the protective factors that were independently associated with low recurrence of endometriosis were postoperative medical treatment (OR = 0.59; 95% CI = 0.42–0.84; P = 0.003) and postoperative pregnancy (OR = 0.34; 95% CI = 0.19–0.62; P < 0.0001). Conclusions: The results of this retrospective analysis of 1080 patients might help predict the prognosis of patients with ovarian endometriosis after conservative surgery and benefit the clinical management of ovarian endometriosis.